Effect of Genotype and Environment on the Glycoalkaloid Content of Rare, Heritage, and Commercial Potato Varieties. Issue 5 (2nd April 2014) - Valcarcel, Jesus; Reilly, Kim; Gaffney, Michael; O'Brien, Nora
Abstract Potatoes accumulate toxic steroidal compounds that could be harmful for humans if consumed in high quantities and must be controlled. In this study, we were interested in assessing the levels and variation of glycoalkaloid content in 60 varieties of potato planted in 2 trial sites over 2 y. Total glycoalkaloid levels ranged from 4 to 957 mg/kg of dry weight in the flesh and from 150 to 8133 mg/kg in the skin, with the latter accumulating generally more α‐chaconine than α‐solanine. Contents in the flesh were below the safe limit for all varieties, but were generally above in the skin. Maximum values in each site and year of cultivation were found for varieties "Beauty of Hebron, " "May Queen, " and "Arran Pilot" in the skin and "Beauty of Hebron, " "International Kidney, " and "Congo" in the flesh. Year of cultivation had a significant effect on total glycoalkaloid content (P < 0.0001), with interactions between variety and site of cultivation and variety and year of cultivation also significant (P < 0.0001), implying that environmental effects seem to act differentially and could induce high levels in genetically predisposed varieties. Practical Application This paper reports the levels of toxic glycoalkaloids in 60 varieties of potato. Dietary intake and safety of consumers is discussed and varieties used by the potato processing industry are assessed in terms of safety and potential use of waste peel as raw material.